Karoo Sanatorium: A Speculative Fiction Based on Many True Stories. Issue 1 (15th February 2022) - Vale, Beth
Summary: In the early twentieth century, with tuberculosis taking hold in many European cities, sanatoriums in South Africa's semi‐arid Karoo region were emerging as prime healing destinations for "consumptive immigrants." Today, the Karoo continues to be marketed as a reprieve from the pathogens of city life, most recently as a "low‐viral escape" amid the COVID‐19 pandemic. Inspired by ethnographic and archival research, this dystopian fiction imagines the contemporary re‐opening of a Karoo sanatorium and the everyday politics in which such a project might be enmeshed. The story is followed by an ethnographic statement that explains some of the research on which the story is based.